Chimeric antigen receptor (CAR) T-cell therapy: Harnessing extracellular vesicles for enhanced efficacy - Beatrice Spokeviciute; Sharad Kholia; Maria Felice Brizzi (Elsevier, 2024)
A cutting-edge approach in cell-based immunotherapy for combating resistant cancer involves genetically engineered chimeric antigen receptor T (CAR-T) lymphocytes. In recent years, these therapies have demonstrated effectiveness, leading to their commercialization and clinical application against certain types of cancer. However, CAR-T therapy faces limitations, such as the immunosuppressive tumour microenvironment (TME) that can render CAR-T cells ineffective, and the adverse side effects of the therapy, including cytokine release syndrome (CRS). Extracellular vesicles (EVs) are a diverse group of membrane-bound particles released into the extracellular environment by virtually all cell types. They are essential for intercellular communication, transferring cargoes such as proteins, lipids, various types of RNAs, and DNA fragments to target cells, traversing biological barriers both locally and systemically. EVs play roles in numerous physiological processes, with those from both immune and non-immune cells capable of modulating the immune system through activation or suppression. Leveraging this capability of EVs to enhance CAR-T cell therapy could represent a significant advancement in overcoming its current limitations. This review examines the current landscape of CAR-T cell immunotherapy and explores the potential role of EVs in augmenting its therapeutic efficacy.